2015
DOI: 10.1007/s10723-015-9330-2
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Science Gateway for the Cherenkov Telescope Array

Abstract: The Cherenkov Telescope Array (CTA) is currently building the next generation, ground-based, very high-energy gamma-ray instrumentation. CTA is expected to collect very large datasets (in the order of petabytes) which will have to be stored, managed and processed. This paper presents a graphical user interface built inside a science gateway aiming at providing CTA-users with a common working framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In general, a science gateway can be defined as a set of software, data collections, instrumentation and computational capabilities that are integrated -using different technologies and middleware [35] -via a Web portal (or a desktop application) in a user friendly and effective environment supporting the scientific research and education activities of a specific community. Science gateways are gaining an increasing interest in many communities [36,37], such as the astrophysics one [38,39,40], also because one of the best strategies to provide software and data to a scientific community is through a set of services designed following this paradigm. The portal we developed in the project and used for involving citizen scientists [6] is based on this paradigm.…”
Section: Citizen Astronomy and Its Implementationmentioning
confidence: 99%
“…In general, a science gateway can be defined as a set of software, data collections, instrumentation and computational capabilities that are integrated -using different technologies and middleware [35] -via a Web portal (or a desktop application) in a user friendly and effective environment supporting the scientific research and education activities of a specific community. Science gateways are gaining an increasing interest in many communities [36,37], such as the astrophysics one [38,39,40], also because one of the best strategies to provide software and data to a scientific community is through a set of services designed following this paradigm. The portal we developed in the project and used for involving citizen scientists [6] is based on this paradigm.…”
Section: Citizen Astronomy and Its Implementationmentioning
confidence: 99%
“…Significant effort has been put in this direction by the EC-funded project AARC [55] (and the recently approved AARC2) towards an interoperable architectural design, policy harmonization and community-driven piloting activity. Some examples of AARC-compliant e-infrastructures are the EGI CheckIn Service [56], the INDIGO-Datacloud [57] Authentication and Authorization Infrastructure (AAI) and the INAF Cherenkov Telescope Array (CTA) AAI, which includes the INAF-CTA Science Gateway [58]. The H2020 VRE4EIC project is also dedicated to definition of an interoperability framework that will enable exchange of resources among science gateways more easily [15].…”
Section: Conferences and Journal Special Issuesmentioning
confidence: 99%
“…Lemos et al's survey identified SHOP2 as the only approach dealing with SWS and Taverna as the only approach dealing with scientific workflows. To the best of our knowledge, there is a lack of approaches for SWS composition in astrophysics apart from certain specific software specifically designed for specific astrophysical instruments like scientific gateway for the instrument CTA [25]. A more generic SWS composition in this field would be highly appreciated by the community.…”
Section: Motivationsmentioning
confidence: 99%
“…If no information is available for a service regarding one of its outputs, a default neutral value is used during the composition for this service rating. If a quality assessment is found for a service concerning one of the outputs that may be useful for the composition, then this value is used for service selection inside the composition (this parameter is tested in lines [23][24][25][26][27][28][29][30][31].…”
Section: Quality Of Service Assessmentmentioning
confidence: 99%